Invasive species in the malacofauna aquatic (Mollusca, Gastropoda, Bivalvia) of the Republic of Moldova - COADĂ, Viorica; ŢÎGANAŞ, Ana; GÎȚU, Ana (Acta et Commentationes Exact and Natural Sciences, 2020)
The paper addresses the problem of invasive species in the aquatic fauna of the Republic of Moldova. Of the three species included in the global register of introduced and invasive species, the highest rate of expansion and the greatest negative effect on the functioning of aquatic ecosystems in the Republic of Moldova is represented by the species Dreissena bugensis (Andrusov, 1897).